Alterations in driver genes are predictive of survival in patients with resected pancreatic ductal adenocarcinoma. Issue 17 (23rd June 2020) - McIntyre, Caitlin A.; Lawrence, Sharon A.; Richards, Allison L.; Chou, Joanne F.; Wong, Winston; Capanu, Marinela; Berger, Michael F.; Donoghue, Mark T. A.; Yu, Kenneth H.; Varghese, Anna M.; Kelsen, David P.; Park, Wungki; et al.
Abstract : Background: KRAS, TP53, CDKN2A, and SMAD4 are established driver genes in pancreatic ductal adenocarcinoma (PDAC). This study was aimed at determining whether the mutational status of driver genes and those involved in DNA repair pathways are associated with clinical outcomes for individuals who undergo resection. Methods: Eligible individuals were those who underwent resection of PDAC and consented to targeted sequencing of their primary tumor via Memorial Sloan Kettering–Integrated Mutation Profiling of Actionable Cancer Targets (MSK‐IMPACT). Genomic alterations were determined on the basis of MSK‐IMPACT results from formalin‐fixed, paraffin‐embedded samples. Associations between genomic alterations and clinical outcomes were assessed. Results: Targeted sequencing was performed on 283 primary tumors resected between 2004 and 2017. The median follow‐up was 23 months among survivors. Alterations in KRAS and TP53 were associated with worse overall survival (OS) in comparison to wild type (median for KRAS, 38.8 months [95% CI, 33.0‐45.5 months] vs 91.0 months [95% CI, 34.8 months to not available (NA)]; P = .043; median for TP53, 37.4 months [95% CI, 32.1‐42.8 months] vs 65.0 months [95% CI, 33.0 months to NA]; P = .035). KRAS G12D mutations were associated with worse OS (median, 31.6 months [95% CI, 25.3‐45.5 months] vs 39.2 months [95% CI, 37.4‐75.2 months]; P = .012). TP53 truncating mutations (median, 39.6 months [95% CI, 32.4‐75.2 months] vs 33.9 months [95% CI, 24.0‐39.0 months]; P = .020) and those associated with loss of heterozygosity (median, 26.6 months [95% CI, 21.6‐44.2 months] vs 39.2 months [95% CI, 34.5‐49.1 months]; P = .048) had decreased OS. TP53 alterations were independently associated with OS in a multivariate analysis (hazard ratio, 1.54; 95% CI, 1.01‐2.33; P = .042). Individuals with germline alterations in homologous recombination deficiency (HRD) genes had improved OS in comparison with those without them (median, not reached vs 37.0 months; 95% CI, 33.0‐49.8 months; P = .035). Conclusions: In patients with resected PDAC, genomic alterations in KRAS and TP53 are associated with worse outcomes, whereas alterations in HRD genes are associated with a favorable prognosis. Further studies are needed to better define these alterations as biomarkers in resected PDAC. Abstract : Results from a routinely used, clinically actionable targeted sequencing panel demonstrate that alterations in KRAS and TP53 are associated with worse outcomes in patients undergoing resection for pancreatic ductal adenocarcinoma. Specifically, KRAS G12D mutations, TP53 alterations resulting in truncations, and TP53 alterations in areas with loss of heterozygosity are associated with a poorer prognosis; in addition, germline homologous repair deficiency mutations are associated with improved overall survival.